Hillforts of the Cheshire Ridge - Garner, D. J. (Archaeopress, 2016)
The Habitats and Hillforts of Cheshire's Sandstone Ridge Landscape Partnership Project was focussed on six of Cheshire's hillforts and their surrounding habitats and landscapes. It aimed to develop understanding of the chronology and role of the hillforts and encourage local interest and involvement in their maintenance.